KATP channels in cerebral hemodynamics: a systematic review of preclinical and clinical studies - Daoud, Hassan Ali Suleiman; Kokoti, Lili; Al-Karagholi, Mohammad Al-Mahdi (Frontiers in Neurology, 2024)
Cumulative evidence suggests that ATP-sensitive potassium (KATP) channels act as a key regulator of cerebral blood flow (CBF). This implication of KATP channels seems to be complicated, since KATP channels are expressed in several vascular-related structures such as smooth muscle cells, endothelial cells and pericytes.In this systematic review, we searched PubMed and EMBASE for preclinical and clinical studies addressing the involvement of KATP in CBF regulation.A total of 216 studies were screened by title and abstract. Of these, 45 preclinical and 6 clinical studies were included. Preclinical data showed that KATP channel openers (KCOs) caused dilation of several cerebral arteries including pial arteries, middle cerebral artery and basilar artery, and KATP channel inhibitor (KCI) glibenclamide, reversed the dilation. Glibenclamide affected neither the baseline CBF nor the baseline vascular tone. Endothelium removal from cerebral arterioles resulted in an impaired response to KCO/KCI. Clinical studies showed that KCOs dilated cerebral arteries and increased CBF, however, glibenclamide failed to attenuate these vascular changes.Endothelial KATP channels played a major role in CBF regulation. More studies investigating the role of KATP channels in CBF-relating structures are needed to further elucidate their actual role in cerebral hemodynamics in human.